Can change leadership impact on staff organizational citizenship behavior? A scenario from Malaysia. Issue 2 (2nd December 2019) - Ghavifekr, Simin; Adewale, Adebayo Saheed
Abstract : Purpose: The purpose of this paper is to explore the impact of change leadership on staff organizational citizenship behavior in a university setting. Moreover, the study aims to explore forces that influencing on staff organizational citizenship behavior in higher education institutions. Design/methodology/approach: The study adopts a qualitative research design. An interview protocol along with field notes were used as major approaches for collecting in-depth data. Coding and categorizing approach were used to analyze interview transcriptions to help for emerging the study's themes. Findings: The findings reveal that change leadership builds confidence of staff, motivate them and helps to ensure trust. Moreover, results show that staff organizational citizenship behavior is influenced by personal, organizational, social-cultural and economic forces. To increase the organizational citizenship behavior of staff in higher education institutions, there is a need for leaders to use appropriate change-oriented style in leading their organizations. Findings also revealed that change leaders must serve as role-model to their subordinates as a way on enhancing staff organizational citizenship behavior. Research limitations/implications: Academic leaders are the pivot of change in higher education institutions. Accordingly, the effectiveness of higher education institution, staff and students are depending on the effectiveness of the leadership. In this regard, academic leaders' willingness to change is the most effective factor that not only sets the credibility of the organization, but, more importantly, influence on staff organizational behavior. Practical implications: It is hoped that the outcome of this research will contribute to the current knowledge of change leadership and organizational behavior in universities. Originality/value: This is an original research and makes a great contribution to higher education in Asian countries.